Optofluidic three-dimensional microfabrication and nanofabrication - Xianglong Lyu; Wenhai Lei; Gaurav Gardi; Muhammad Turab Ali Khan; Shervin Bagheri; Mingchao Zhang; Metin Sitti (Nature, 2026)
Abstract Three-dimensional (3D) microfabrication/nanofabrication technologies have revolutionized various fields by enabling the precise construction of complex microstructures/nanostructures 1–6 . However, existing methods face challenges in fabricating intricate 3D architectures from a diverse range of materials beyond conventional polymers. Here we introduce a universal 3D microfabrication/nanofabrication strategy compatible with a broad range of materials by precisely manipulating optofluidic interactions within a confined 3D space, enabling the creation of volumetric, free-form 3D microstructures/nanostructures. A femtosecond-laser-induced heating spot generates a localized thermal gradient, providing precise spatiotemporal control over optofluidic interactions of the nanoparticle-laden dispersions. This enables the rapid and highly localized assembly of nanoparticles with diverse shapes and compositions—including metals, metal oxides, carbon nanomaterials and quantum dots—into complex 3D microstructures. To demonstrate its versatility, we fabricate multifunctional microdevices, such as 3D microfluidic valves with size-selective sieving functionality, achieving fast separation of microparticles/nanoparticles with distinct dimensions, as well as microrobots integrated with four distinct functional materials, achieving multimodal locomotion powered by different external stimuli. This optofluidic 3D microfabrication/nanofabrication method unlocks new opportunities for advanced material innovation and miniaturized device development, paving the way for broad applications in colloidal robotics 7 , microphotonics/nanophotonics, catalysis and microfluidics.